Erosion - Graham, Jorie, 1950- (Book collections on Project MUSE., 1983)
Jorie Graham grew up in Italy and now lives in northern California. She has received grants from the Ingram-Merrill Foundation, the Bunting Institute, and the John Simon Guggenheim Memorial Foundation. Her first book, Hybrids of Plants and of Ghosts (Princeton, 1980), won the Great Lakes Colleges Association Award as the best first book of poems published in 1980.